Islamic Values and Sasak Local Wisdoms: The Pattern of Educational Character at NW Selaparang Pesantren, Lombok - Nashuddin Nashuddin (Universitas Islam Negeri Mataram, 2020)
This study aims to analyze the relevance of Islamic values to the local cultural values of Sasak Lombok community, and the role of pondok pesantern (Islamic boarding schools) in integrating both of them in building student character in educational practices. This is important because there is a phenomenon that certain religious group contradistinguish between Islam and local traditions. Even in many cases local traditions are considered to lead to heresy and novelty. Through field studies with a qualitative approach, and applying Thomas Lickona's theory as the theoretical framework, this study argues that substantively, Islam and local culture have relevance to the local traditions of Sasak society. In this context, pondok pesantren have a strategic role that successfully integrates the two. On the one hand, pondok pesantren grows from the community itself, and on the other hand, it is also an Islamic educational institution. This position makes it possible for pondok pesantren to maintain the character of the santri by integrating local culture and religion as the basis for character education. Practically, the pattern of character development based on the wisdom of Sasak culture is carried out through three stages: moral knowing, moral feeling, and moral action. These three stages succeeded in bringing together Islam and the local tradition of Sasak in educational practice.